EXTH-40. MULTIDIMENSIONAL INTERROGATION OF GLIOBLASTOMA MICROENVIRONMENT TREATMENT RESPONSE IN EXPLANT CULTURES. (12th November 2021) - Shekarian, Tala; Bartoszek-Kandler, Ewelina; Zinner, Carl; Schuerch, Christian; Hutter, Gregor
Abstract: The immune tumor microenvironment (iTME) of glioblastoma (GBM) contains microglial, macrophage, other myeloid cell populations and as adaptive immune cells. Recent therapeutic strategies for GBM aim at targeting iTME components to induce antitumoral immunity. A patient-tailored, ex vivo drug testing and response analysis platform would facilitate personalized therapy planning, provide insights into treatment-induced immune mechanisms in the iTME, and enable the discovery of biomarkers of response and resistance. Here, we generated patient-derived, live 3D GBM bioreactors from different tumor regions to assess iTME treatment responses to microglia modulators and immune checkpoint inhibitors. Intact GBM tissue specimens from the tumor center and periphery were cultured for 7 days in the presence or absence of anti-PD1, anti-CD47 antibodies or their combination. Tissues were analyzed by CODEX highly multiplexed microscopy using an immune-centered 54-marker panel, and changes in cytokine and chemokine levels in culture supernatants were investigated. A computational pipeline for integrative therapy response assessment was implemented. Explant cultures from n=8 IDH wt GBM were subjected to this integrative personalized analysis. Tissue integrity after 3D bioreactor cultures was comparable to tissue taken directly after surgery. FFPE CODEX workflow was feasible with adequate staining quality in bioreactor cultures. 850'000 single cells were segmented and clustered. Cellular composition between tumor center and the peripheral invasion zone differed significantly in immune phenotypes, cytokine profile and response to innate, adaptive or combinatorial local immunotherapies. Multiplexed cytokine analysis revealed IFNγ response signatures in a subset of center samples, whereas the peripheral invasion zone displayed a blunted cytokine response. This cytokine signature corresponded to cellular composition shifts within specific cellular neighborhoods. CD4 and CD8 T cells were invigorated and left their vascular niche. Our study demonstrates that local immunotherapies enable an active antitumoral immune response within the tumor center, and provides a multidimensional personalized framework for immunotherapy response assessment.